D-arabinose acts as antidepressant by activating the ACSS2-PPARγ/TFEB axis and CRTC1 transcription - Yaxin Guo; Nuo Chen; Ming Zhao; Baihui Cao; Faliang Zhu; Chun Guo; Yongyu Shi; Qun Wang; Yan Li; Lining Zhang (Elsevier, 2024)
CREB-regulated transcription coactivator 1 (CRTC1), a pivotal synaptonuclear messenger, regulates synaptic plasticity and transmission to prevent depression. Despite exhaustive investigations into CRTC1 mRNA reductions in the depressed mice, the regulatory mechanisms governing its transcription remain elusive. Consequently, exploring rapid but non-toxic CRTC1 inducers at the transcriptional level is important for resisting depression. Here, we demonstrate the potential of D-arabinose, a unique monosaccharide prevalent in edible-medicinal plants, to rapidly enter the brain and induce CRTC1 expression, thereby eliciting rapid-acting and persistent antidepressant responses in chronic restrain stress (CRS)-induced depressed mice. Mechanistically, D-arabinose induces the expressions of peroxisome proliferator-activated receptor gamma (PPARγ) and transcription factor EB (TFEB), thereby activating CRTC1 transcription. Notably, we elucidate the pivotal role of the acetyl-CoA synthetase short-chain family member 2 (ACSS2) as an obligatory mediator for PPARγ and TFEB to potentiate CRTC1 transcription. Furthermore, D-arabinose augments ACSS2-dependent CRTC1 transcription by activating AMPK through lysosomal AXIN-LKB1 pathway. Correspondingly, the hippocampal down-regulations of ACSS2, PPARγ or TFEB alone failed to reverse CRTC1 reductions in CRS-exposure mice, ultimately abolishing the anti-depressant efficacy of D-arabinose. In summary, our study unveils a previously unexplored role of D-arabinose in activating the ACSS2-PPARγ/TFEB-CRTC1 axis, presenting it as a promising avenue for the prevention and treatment of depression.